(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract This review article discusses and critically analyzes five theories used to explain spontaneous urbanization and how humans and their behaviour affect urban and architectural structures, in addition to defining both spontaneous urbanization and social sustainability. These theories are (Theory of the spontaneous evolution of social institutions, living systems theory, overlapping space theory, right to the city theory and social capital theory). The importance of the research is highlighted by the necessity of studying and analyzing the theories of spontaneous urbanization and extracting social principles and values, as the success of the spontaneous environment stems from comprehensive and balanced thinking in various aspects of life-related to humans and their social and cultural requirements.The importance of finding a solution to the increase in human gatherings in the urban environment and the inability of the plan to keep pace with the construction of the population in poor areas and informal (spontaneous) settlements that were the result of local residents' initiatives and efforts to adapt to the rapidly changing environment. The importance of benefiting from the development of civil society and encouraging and strengthening local customs. Theory of the spontaneous evolution of social institutions, living systems theory and social capital theory each focus on the individual and society through the interactions of individuals, groups and social networks and the impact of human behaviour on the physical environment, although living systems theory focuses on the city being a biological structure that adapts and evolves in its surroundings. The two theories (overlapping space theory, and right to the city theory) focused on space and place from a legal, rights and social perspective, which emphasized how urban spaces are used and how they are spontaneously reshaped by residents, such as the right to social participation in urban decision-making, institutional diversity and the right to use space. Each theory contributed to analyzing an aspect of spontaneous urbanization, and the researcher concluded that they complement each other to reach an integrated model of spontaneous urbanization, to reach the indicators and principles that have been extracted from theories towards sustainable social development.